1971
DOI: 10.1121/1.1912373
|View full text |Cite
|
Sign up to set email alerts
|

The Acoustic Stapedius Reflex in Relation to Critical Bandwidth

Abstract: The threshold of the acoustic stapedius reflex in man was investigated by means of changes in acoustic impedance of the ear. The contralateral ear was stimulated by using bands of noise and complex tones with various bandwidths. The experiments showed that the reflex threshold, expressed in decibels re 2.10 -5 N/m •', is almost constant for bandwidths less than a specific value and designated as "critical bandwidth." When the bandwidth was further increased, a decrease in the reflex threshold at approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 2 publications
(2 reference statements)
2
23
0
Order By: Relevance
“…It has also been revealed that, for a given intensity, broadband noise will elicit a larger change in impedance than that associated with a pure tone (Block & Wightman, 1977;Flottorp, Djupesland, & Winther, 1971; 11 Margolis & Popelka, 1975). This implies that the AR is sensitive to a change in loudness that results from increasing the bandwidth of a stimulus maintained at a constant SPL.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been revealed that, for a given intensity, broadband noise will elicit a larger change in impedance than that associated with a pure tone (Block & Wightman, 1977;Flottorp, Djupesland, & Winther, 1971; 11 Margolis & Popelka, 1975). This implies that the AR is sensitive to a change in loudness that results from increasing the bandwidth of a stimulus maintained at a constant SPL.…”
Section: Introductionmentioning
confidence: 99%
“…Others have demonstrated that when stimuli such as pure tones and noise bands are matched for loudness, the magnitudes of the elicited acoustic reflexes are similar (Block et al, 1977;Gorga, Lilly, & Lenth, 1980). Some investigators have hypothesized that a critical band exists for the acoustic reflex (Flottorp et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the extension of the band width is wider, there is no change up to the critical point. If the stimulating band width is continuously increased, there is a linear decrease of the re lex threshold [2,3,52], igure 3, he critical bandwidth is the width of the sound band in which suddenly there is changed some subjective hearing constants, mainly loudness, while the overall sound intensity stays constant.…”
Section: Stimulation Length (Time)mentioning
confidence: 99%